2015
DOI: 10.1051/sicotj/2015008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effectiveness of a non-governmental organization in supporting clubfoot clinic at a tertiary care center

Abstract: Background: Since December 2011, a non-governmental organization (NGO) has been associated with our clubfoot clinic. Debates related to the effectiveness of NGOs in clinical milieu have raged on for a long time. The aim of this study was to analyze the effectiveness of an NGO in supporting the running of a clubfoot clinic in a tertiary care center. Methods: A descriptive, observational study was conducted from October to December 2014. The three main conceptualizations of effectiveness namely goals, resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Another Indian study conducted in 2014 showed that 42% clubfoot patients were under 6 weeks of age when first enrolled for treatment. 6 This clearly does not match with international recommendation of introducing Ponseti treatment soon after birth. The male-female ratio in our study was similar to that reported in world literature.…”
Section: Discussionmentioning
confidence: 89%
“…Another Indian study conducted in 2014 showed that 42% clubfoot patients were under 6 weeks of age when first enrolled for treatment. 6 This clearly does not match with international recommendation of introducing Ponseti treatment soon after birth. The male-female ratio in our study was similar to that reported in world literature.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies 6 7 20 21 22 23 24 25 26 27 28 have been undertaken to study the validity and interobserver reliability of Pirani scoring system among trained health personnel [ Table 6 ]. Cosma andVasilescu 24 in a study to determine the reproducibility of Pirani and Dimeglio classification systems found a high Pearson's coefficient correlation (>0.85) for both the systems.…”
Section: Discussionmentioning
confidence: 99%
“…Counsellors form an essential part of the clubfoot treatment program. 28 These are nonmedical personnel usually associated with an NGO who lend their support to the working of a clubfoot clinic. Their efficiency in effective and accurate Pirani scoring can be of great advantage to the clubfoot team.…”
Section: Discussionmentioning
confidence: 99%